Affective Commitment as Mediator Variable: Authentic Leadership towards Organizational Learning in Bank X - Danan Prima Nanda; Zamralita Zamralita; Rita Markus Idulfilastri (Eduvest - Journal of Universal Studies, 2024)
Nowadays, organizations are required to continue to innovate and adapt to challenges that may affect the achievement of business goals. The effort that can be done is to optimize the implementation of Organizational Learning. Organizational Learning cannot be carried out optimally without the role of superiors and employees. Therefore, the role of superiors in implementing Authentic Leadership needs to be considered. But Authentic Leadership is not enough to explain Organizational Learning. The existence of Authentic Leadership has the probability of creating a supportive and open environment so that it has an impact on increasing affective commitment to employees. Based on this explanation, the purpose of this study was to examine the influence of Authentic Leadership on Organizational Learning mediated by Affective Commitment. The sample of this research were employees at Bank X, consumer credit department and 216 subjects were obtained using the Accidental Sampling method. Data processing is done using PROCESS. The results showed that Authentic Leadership had a significant effect on Organizational Learning mediated by Affective Commitment with a BootLLCI value of 0.0041 and a BootULCI value of 0.0892. This type of mediation is Partial Mediation. Based on the results of this research, Organizational Learning can be optimized through the application of Authentic Leaders so that it can encourage the creation of affective commitment so that in the end employees are willing to give their best by developing knowledge or insights that can be used by the organization as a whole.